2014
DOI: 10.1530/eje-14-0371
|View full text |Cite
|
Sign up to set email alerts
|

Small cerebellar cortex volume in patients with active Cushing's syndrome

Abstract: The cerebellar cortex volume is smaller in active CS patients than in controls. This finding is associated with poor visual memory and quality of life and is mostly pronounced in patients with higher triglyceride levels and older age at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 45 publications
2
57
0
1
Order By: Relevance
“…In agreement, Bourdeau et al (15) demonstrated that patients with active CS had increased third ventricle diameter, bicaudate diameter, and cerebral atrophy, compared with control patients with no sellar tumors. A recent study has found smaller grey matter volumes of the bilateral cerebellum in patients with active CS compared with controls (19). When investigating the effect of CS on the developing brain, children with CS were found to have smaller cerebral volumes, larger ventricles and smaller amygdala than controls (27).…”
Section: Mri Outcome In Patients With Active Csmentioning
confidence: 91%
See 2 more Smart Citations
“…In agreement, Bourdeau et al (15) demonstrated that patients with active CS had increased third ventricle diameter, bicaudate diameter, and cerebral atrophy, compared with control patients with no sellar tumors. A recent study has found smaller grey matter volumes of the bilateral cerebellum in patients with active CS compared with controls (19). When investigating the effect of CS on the developing brain, children with CS were found to have smaller cerebral volumes, larger ventricles and smaller amygdala than controls (27).…”
Section: Mri Outcome In Patients With Active Csmentioning
confidence: 91%
“…Review C D Andela and others MRI studies in Cushing's syndrome criteria, but mentioned criteria of remission (15,16,17,18,19). One study did neither describe diagnostic nor remission criteria (20).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…Depression, anxiety and cognitive dysfunction are common in CS, especially in the active phase, although the so-called 'cured' patients still complain of a lower general well-being, more anxiety and depression, and impaired QoL when compared to matched healthy controls (49,56,57,58). Furthermore, after successful treatment, it often takes several months or even more than 1 year to perceive improvements.…”
Section: Cushing's Diseasementioning
confidence: 99%
“…10,13,25 Another region of potential reduction of volume is the cerebellum, which is prone to atrophic degeneration in long-term hypercortisolism. 28,31 Most studies regarding brain atrophy in CD or Cushing's syndrome (CS) are based on subjective evaluation of MR images and manual measurements of different regions of interest. 6,32,34 Studies based on objective, voxelbased measurements of brain atrophy in CD are very rare and have dealt with patients in long-term remission from CD.…”
mentioning
confidence: 99%